The urban refill a compact community and land utilization model - Madrogaba, Christian Andro N.
The Urban Refill is a compact community and land utilization model that responded to some of the most prominent urban issues including the need for more decent housing, the need for more healthful environments, the weakening of city linkages, and the need to keep green and open spaces. "Refill" is a neologism and derivative of "Infill." The model made use of the core principles of infilling as it proposed the use of idle "pocket of spaces" in between buildings on densely populated regions and fill them with a flexible, modularly coordinated building system. In the process, a network of "refills" is created, solving the aforementioned issues incrementally and holistically.